Indonesian Pre-Service English Teachers’ Teaching Anxiety in Teaching English for Occupational Purposes Classes - Reni Andriani; Adaninggar Septi Subekti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: This study aims at investigating Indonesian pre-service English teachers’ Foreign Language Teaching Anxiety (FLTA) in teaching English for Occupational Purposes (EOP) classes and to explore the factors of FLTA. The participants were six pre-service English teachers. The study employed a qualitative design and used observations and interviews as the methods of data collection. The study found that pre-service teachers experienced anxiety when opening the class, when students asked questions, and when they had mispronunciation or forgot certain vocabulary. Through Thematic Analysis, the study also found five contributing factors to the participants’ teaching anxiety. These were perceived lack of EOP teaching experience and lack of content knowledge, lack of confidence in their English, teaching mixed-abilities students and teaching students older than them.